Pengetahuan Lokal Banyuwangi dalam Program Kuliner Kompas TV - Nurislaminingsih, Rizki; Perdana, Fitri; Heriyanto, Heriyanto (HUMANIKA, 2025)
This study aims to identify the forms of indigenous knowledge embedded in Banyuwangi's traditional cuisine, as presented in Kompas TV culinary programs uploaded to YouTube. Using a qualitative approach and textual analysis of selected video content, the findings revealed that Banyuwangi cuisine contains various forms of local health-related knowledge. This includes the use of plants such as Marsilea crenata (water clover), guava leaves, Sesbania grandiflora (hummingbird tree flowers), and lemongrass, which have been scientifically proven to contain active compounds beneficial to health. Local communities also demonstrate expertise in food fermentation, such as tofu, soy-based sweet soy sauce, and nata de soya, as well as in the processing of coffee beans and leaves into health drinks. This study identifies the traditional use of wadung leaves and fruit as culinary spices, which, despite the lack of existing scientific studies, offers potential for further research in the health and chemistry fields. These findings highlight that indigenous knowledge not only preserves tradition and supports health but also contributes significantly to the creative economy. Banyuwangi's local gastronomy, when packaged in digital media content, has strong potential to become part of a sustainable and inclusive cultural and creative industry.